2015
DOI: 10.1142/s0219519415500426
|View full text |Cite
|
Sign up to set email alerts
|

Peristaltic Flow of Couple-Stress Fluid With Heat and Mass Transfer: An Application in Biomedicine

Abstract: Analysis is performed for the simultaneous effects of heat and mass transfer on the peristaltic transport of an electrically conducting couple-stress fluid in a compliant walls channel. The study may be useful in understanding the physiological flow of blood through micro-circulatory system in the presence of particle-size effect. Long wavelength and low Reynolds number aspects are taken into consideration. Exact solutions for stream function, temperature and concentration are derived. Impact of pertinent para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Then Shapiro et al 2 have extended the research work of peristalsis. Later, Hina et al 3 have studied the peristaltic flow of couple stress fluid and Powell-Eyring fluid and concluded that their analysis was helpful in applications of biomedicine. Ahmed et al 4 have discussed the biofluid flow driven by peristaltic propulsion in a curved channel with the impact of Brinkman number and Hartmann number and revealed that amplitude of heat transfer coefficient decreases with the enhancement of curvature parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Then Shapiro et al 2 have extended the research work of peristalsis. Later, Hina et al 3 have studied the peristaltic flow of couple stress fluid and Powell-Eyring fluid and concluded that their analysis was helpful in applications of biomedicine. Ahmed et al 4 have discussed the biofluid flow driven by peristaltic propulsion in a curved channel with the impact of Brinkman number and Hartmann number and revealed that amplitude of heat transfer coefficient decreases with the enhancement of curvature parameter.…”
Section: Introductionmentioning
confidence: 99%
“…A clear example of this movement is the movement of urine from the kidney to the bladder, the movement of food within the gastrointestinal tract, and also the movement of eggs within the fallopian tube and so on. Hayat et al, [7] have studied peristaltic flow of couple-stress fluid with heat and Mass Transfer: An application in biomedicine. Noreen [8] discussed the Peristaltic flow of a tangent hyperbolic fluid with convective boundary condition.…”
Section: Introductionmentioning
confidence: 99%
“…Since, the most alluring work was described by Latham, 1 various authors investigated analytically, numerically and experimentally the mechanism of peristaltic flow in different geometrical aspects. [2][3][4][5] For instance, Hina et al 6 explored the impact of compliant walls on non-Newtonian peristaltic motion of third grade fluid in a curved channel and obtained the series solution for temperature profile and concentration profile. He observed that the magnitude of the bolus in not similar in the upper and the lower part of the channel.…”
Section: Introductionmentioning
confidence: 99%